PENGARUH PEMBERDAYAAN DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) TERHADAP KINERJA PEGAWAI DENGAN BUDAYA ORGANISASI SEBAGAI VARIABEL MODERASIâ (Studi Kasus di Sekretariat Daerah Kabupaten Batang - Asep Dwi Nugroho, 10.42.02.0116 (Students Journal of Economic and Management, 2013)
This study aims to examine and analyze the influence of empowerment and Organizational Citizenship Behavior (OCB) on employee performance within moderating variable of organizational culture at the Secretariat of Batang Regency. Technique of data examination used in this research include test validity, test reliability, multiple regression analysis, Model Test (Test F and R2) and moderation tests to prove the research hypothesis. Tested the validity of the data collected by the method of factor analysis and tested for reliability with coefficient alpha (Cronbach Alpha). The data are valid and reliability test results show the number 0,7205 for empowerment variables, 0,7755 for the Organizational Citizenship Behavior (OCB) variables, 0,8204 for the variable of organizational culture and 0,6111 for the variable of employee performance. Results of the analysis and discussion show that empowerment and Organizational Citizenship Behavior (OCB) has positive influence on employee performance, proven organizational culture moderates the influence of empowerment on employee performance, proven organizational culture moderates the Organizational Citizenship Behavior (OCB) on employee performance. Keywords : Empowerment, Organizational Citizenship Behavior (OCB), Organizational Culture and Employee Performance.